High-strength aluminum alloy and preparation method and application thereof
By preparing anti -aluminum powder in the inert gas atmosphere and mixing with other additives, combining compaction, sintering and plastic deformation processing, solve the problem of the combination of aluminum oxide membranes in the powder metallurgical method, obtaining high strength and high density density. The aluminum alloy significantly improves the performance of the material.
Patent Information
- Application Number
- CN202411445723.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
During the forming and sintering process, the existing powder metallurgy process has hindered the metallurgical bonding due to the irreducible alumina film on the surface of the aluminum-based powder, making it difficult to obtain high-density, clean interface aluminum alloys and composite materials, resulting in poor material performance.
Aluminum powder is prepared in an atmosphere filled with inert gas, and epoxy zinc phosphate is sprayed to isolate the air and prevent the aluminum powder from oxidizing. The anti-oxidation aluminum powder is then mixed with other additives such as titanium nitride, boron carbide, nano-zinc powder, etc., and undergoes compaction, sintering and plastic deformation processing to form a high-strength aluminum alloy.
Reduce the adverse effects of aluminum oxide film, improve the intensity and density of aluminum alloy, cleanliness, dense structure, and intensive performance and comprehensive performance.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of aluminum alloys, and in particular to a high-strength aluminum alloy and a preparation method and application thereof. Background Art
[0002] Aluminum alloys and their composite materials have the characteristics of low density, high specific strength, corrosion resistance and easy surface treatment, so they are widely used in industries such as construction, packaging, transportation, electrical and electronics, machinery manufacturing, aerospace, petrochemicals and people's daily lives.
[0003] The commonly used methods for preparing aluminum alloys and composite materials are mainly melt casting and powder metallurgy. Based on the melt casting process, such as improving purity, adjusting composition, changing heat treatment specifications, etc., the effect of developing new aluminum-based materials has become increasingly small. The use of powder metallurgy can not only avoid material component segregation, but also improve solid solubility, obtain some aluminum alloys that cannot be produced by melt casting, and can refine the organization and improve its morphology and distribution characteristics. Compared with aluminum alloys with similar composition prepared by melt casting, aluminum alloys prepared by powder metallurgy have better physical, chemical and mechanical properties.
[0004] However, since the surface of aluminum-based powders will inevitably be covered with a dense, irreducible aluminum oxide film, the powder metallurgy method will hinder the formation of metallurgical bonding between particles during the forming and sintering process. It is often difficult to obtain high-density, clean-interface aluminum alloys and composite materials through conventional powder metallurgy processes, resulting in poor material performance. Summary of the invention
[0005] The present application aims to overcome at least one of the defects of the prior art and provide a high-strength aluminum alloy and a preparation method and application thereof, which reduces the adverse effects of the aluminum oxide film through a specific method, makes it easier to form a metallurgical bond between the raw materials and the aluminum, makes the material interface clean and the structure dense, and improves the strength of the aluminum alloy.
[0006] In a first aspect, the present invention provides a method for preparing a high-strength aluminum alloy, which is achieved by the following technical solutions:
[0007] A method for preparing a high-strength aluminum alloy comprises the following steps:
[0008] (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and a pipeline with inert gas, crushing the aluminum blocks with rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder;
[0009] (2) uniformly mixing 80-100 parts of the antioxidant aluminum powder described in step (1) with 3-5 parts of titanium nitride, 2-4 parts of boron carbide, 10-15 parts of nano zinc powder, 3-5 parts of vanadium powder, 2-3 parts of magnesium powder, 10-15 parts of calcium aluminum alloy powder, 1-3 parts of zirconium dioxide powder, 0.5-1 parts of borax powder, and 0.2-0.5 parts of gallium oxide powder according to weight parts to obtain a mixture;
[0010] (3) feeding the mixed material into a product mold preset in a press for compacting to form a formed ingot, and demolding the ingot;
[0011] (4) placing the ingot described in step (3) into a protective atmosphere sintering furnace, passing the protective gas for half an hour to remove the oxidizing atmosphere in the furnace chamber, and sintering the ingot in the sintering furnace at a temperature of 750-850° C. and under a uniaxial pressure to obtain a sintered aluminum alloy;
[0012] (5) Extruding, rolling and forging the sintered aluminum alloy in step (4) to obtain a high-strength aluminum alloy;
[0013] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0014] The surface of the boron carbide is plated with an iron-nickel alloy layer.
[0015] A method for preparing a high-strength aluminum alloy according to an embodiment of the present application has at least the following beneficial effects:
[0016] The present application adopts powder metallurgy to prepare aluminum alloy. Aluminum powder is prepared in an atmosphere filled with inert gas, and epoxy zinc phosphate is sprayed to isolate the air and prevent oxidation of the aluminum powder surface, thereby improving safety and reducing the adverse effects of aluminum oxide film on the aluminum alloy. At the same time, through the combination of various raw materials, the bonding between atoms in the aluminum alloy is made stronger, the interface of the aluminum alloy is made clean, and the structure is dense. Then, through plastic deformation processing methods such as extrusion, rolling, and forging, the grains can be further refined and the mechanical properties and comprehensive properties of the aluminum alloy can be improved.
[0017] The ingot in the present application is subjected to sintering hot pressing treatment, and the combined action of high temperature and pressure forms a metallurgical bond between the powder particles. The external pressure promotes the slip and rearrangement between the powder particles, accelerates the material transfer process, thereby achieving rapid densification of the material and further improving the density and strength of the material.
[0018] The epoxy zinc phosphate of the present application is a composite material composed of epoxy resin and zinc phosphate, which not only has high strength, high toughness, and resistance to chemical corrosion, but also has excellent anti-rust and weather resistance. After being sprayed on the surface of aluminum powder, it can prevent the aluminum powder from contacting with the air and reduce the oxidation of the aluminum powder.
[0019] The phosphorus element in epoxy zinc phosphate is a good alloying element that can form uniform alloying precipitates with aluminum to improve the strength and toughness of aluminum alloys. The addition of phosphorus can improve the wear resistance of aluminum alloys, making them exhibit better durability in friction and wear environments, which is particularly important for applications that need to withstand high friction, such as automotive braking systems, mechanical parts, etc.; the compounds formed by phosphorus and aluminum oxide can effectively prevent and control the oxidation process, thereby improving the corrosion resistance of aluminum alloys; phosphorus can form alloying precipitates with aluminum that have a blocking effect. These precipitates can inhibit intergranular corrosion and pitting corrosion of the material, thereby further improving the corrosion resistance of aluminum alloys; the addition of phosphorus can also refine the grains of aluminum alloys, which helps to improve the plasticity and strength of the alloy. Refined grains mean more grain boundaries, which can more effectively disperse and resist external forces.
[0020] Zinc in the present application is the main liquid phase forming element, which produces an instantaneous liquid phase during the sintering process to achieve sintering densification; the magnesium element has a fast diffusion rate and can quickly break down the small amount of oxide film that may exist on the surface of the aluminum powder, forming a semi-continuous MgO and MgAl2O4 oxide layer at the grain boundary, and at the same time forming a MgZn2 reinforcement phase with the Zn element; zirconium dioxide powder, on the one hand, acts as a reinforcement phase to form uniform and fine dispersed hard particles, thereby improving the hardness, corrosion resistance and fatigue strength of the aluminum alloy, and also protecting the aluminum alloy from oxidation and damage; vanadium powder can be used to improve the toughness of the aluminum alloy.
[0021] The titanium nitride in the present application has a high melting point and high hardness. In the process of preparing aluminum alloy by powder metallurgy, the addition of titanium nitride can optimize the microstructure of the aluminum alloy. During the sintering process, the titanium nitride particles will be evenly distributed in the aluminum matrix to form a dense microstructure, which helps to reduce defects and pores inside the material and improve the density and strength of the material. Through powder metallurgy, titanium nitride powder is mixed with aluminum powder and sintered to prepare a TiN / Al-based composite material. When subjected to external force, the titanium nitride particles can bear part of the load, thereby improving the overall mechanical properties of the material.
[0022] The boron carbide in the present application is a material with high hardness, high strength and high wear resistance. Its hardness is as high as 3000HV, which is 2 to 3 times that of steel. In the process of preparing aluminum alloy by powder metallurgy, boron carbide particles can be used as a reinforcing phase to significantly improve the hardness and strength of the aluminum alloy; after the surface of boron carbide is plated with iron-nickel alloy, the affinity of boron carbide can be improved, the wettability of the molten pool to boron carbide can be improved, and the distribution uniformity of boron carbide particles can be improved.
[0023] The calcium element in the calcium-aluminum alloy can improve the strength of the aluminum alloy by forming compounds with aluminum in the aluminum alloy. The presence of calcium-aluminum compounds makes the crystal lattice in the alloy more uniform and strengthens the grain boundary strength, thereby improving the overall strength of the alloy and significantly improving its corrosion resistance.
[0024] Calcium may inhibit the beneficial effects of phosphorus in aluminum alloys. The inhibitory effects of calcium and phosphorus can be alleviated by adding borax powder.
[0025] The surface of the titanium nitride of the present application is coated with a tin-lead alloy layer, which can improve the affinity of titanium nitride, improve the wettability of the molten pool to titanium nitride, and help improve the distribution uniformity of titanium nitride particles. The tin element in the tin-lead alloy can reduce the surface tension of the liquid phase, making it easier for the liquid phase generated during the sintering process to fill the pores. In addition, during the sintering process, the liquid phase tin can spread on the surface of the aluminum powder, reducing the nitridation rate of the aluminum powder and improving the sintering performance.
[0026] According to some embodiments of the present application, the inert gas in step (1) is selected from one of nitrogen, helium, neon and argon.
[0027] According to some embodiments of the present application, the weight percentage of calcium in the calcium aluminum alloy in step (2) is 5%-10%.
[0028] According to some embodiments of the present application, the compaction pressure in step (3) is 100-1000 MPa. Controlling the compaction pressure during the compaction process can ensure the density and strength of the billet. During the compaction process, due to the effect of pressure, deformation and plastic flow occur between the powder particles, the particles gradually fit together, the gaps are eliminated, and the density of the material is improved.
[0029] According to some embodiments of the present application, the heating rate of the sintering in step (4) is 10-15°C / min.
[0030] According to some embodiments of the present application, the sintering time in step (4) is 1-3 hours.
[0031] According to some embodiments of the present application, the uniaxial pressure during the sintering in step (4) is 20-50 MPa; for example, the uniaxial pressure during the sintering in step (4) is 30 MPa.
[0032] According to some embodiments of the present application, the protective gas in step (4) is selected from one of nitrogen, helium, neon and argon.
[0033] According to some embodiments of the present application, the average particle size of the boron carbide is 2-8 μm, for example, the average particle size of the boron carbide quartz sand is 5 μm. This particle size can better balance the wear resistance and powder fluidity of the aluminum alloy material, and is more conducive to improving the mechanical properties of the aluminum alloy material.
[0034] According to some embodiments of the present application, the average particle size of the titanium nitride is 2-8 μm. This particle size can better balance the wear resistance and powder fluidity of the aluminum alloy material, and is more conducive to improving the mechanical properties of the aluminum alloy material.
[0035] According to some embodiments of the present application, the extrusion in step (5) is performed by equal-diameter angular extrusion, which facilitates grain refinement of aluminum alloy materials and can effectively improve mechanical properties such as strength, hardness, plasticity and toughness of aluminum alloys, while improving their processing properties and corrosion resistance.
[0036] In a second aspect, an embodiment of the present application provides a high-strength aluminum alloy made using the above-mentioned method for preparing a high-strength aluminum alloy.
[0037] The high-strength aluminum alloy according to the embodiment of the present application has at least the following beneficial effects:
[0038] The high-strength aluminum alloy of the present application reduces the adverse effects of aluminum oxide film through a specific method, and it is easier to form a metallurgical bond between the raw materials and the aluminum. The prepared high-strength aluminum alloy material has a clean interface and a dense structure. It is not only high in strength but also light in weight.
[0039] On the third aspect, the embodiments of the present application provide the application of the above-mentioned high-strength aluminum alloy in automobile manufacturing and aerospace. DETAILED DESCRIPTION
[0040] To make the purpose, technical solution and advantages of the present application clearer, the following will be further described in detail in conjunction with specific embodiments. The embodiments described here are only part of the embodiments of the present application and cannot be understood as limiting the scope of protection of the present application.
[0041] Example 1
[0042] Preparation of high-strength aluminum alloy:
[0043] (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with the rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder;
[0044] (2) uniformly mixing, by weight, 90 parts of the antioxidant aluminum powder described in step (1), 4 parts of titanium nitride with an average particle size of 5 μm, 3 parts of boron carbide with an average particle size of 5 μm, 13 parts of nano zinc powder, 4 parts of vanadium powder, 2.5 parts of magnesium powder, 12 parts of calcium aluminum alloy powder, 2 parts of zirconium dioxide powder, 0.8 parts of borax powder, and 0.3 parts of gallium oxide powder to obtain a mixture;
[0045] (3) feeding the mixed material into a preset product mold of a press and compacting it at a pressing pressure of 800 MPa to form a formed ingot, and demolding the ingot;
[0046] (4) placing the ingot prepared in step (3) into a neon atmosphere sintering furnace, passing neon for half an hour to remove the oxidizing atmosphere in the furnace chamber, and sintering the ingot for 2 hours at a temperature of 800° C. and a uniaxial pressure of 30 MPa at a heating rate of 12° C. / min in the sintering furnace to obtain a sintered aluminum alloy;
[0047] (5) Extruding, rolling and forging the sintered aluminum alloy of step (4) by equal-diameter angular extrusion to obtain a high-strength aluminum alloy;
[0048] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0049] The surface of the boron carbide is plated with an iron-nickel alloy layer;
[0050] The weight percentage of calcium in the calcium-aluminum alloy in step (2) is 8%.
[0051] Example 2
[0052] Preparation of high-strength aluminum alloy:
[0053] (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with the rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder;
[0054] (2) uniformly mixing 80 parts of the antioxidant aluminum powder described in step (1) with 5 parts of titanium nitride with an average particle size of 2 μm, 2 parts of boron carbide with an average particle size of 8 μm, 15 parts of nano zinc powder, 3 parts of vanadium powder, 3 parts of magnesium powder, 10 parts of calcium aluminum alloy powder, 3 parts of zirconium dioxide powder, 0.5 parts of borax powder, and 0.5 parts of gallium oxide powder according to weight parts to obtain a mixture;
[0055] (3) feeding the mixed material into a preset product mold of a press and compacting it at a pressing pressure of 100 MPa to form a formed ingot, and demolding the ingot;
[0056] (4) placing the ingot of step (3) into a neon atmosphere sintering furnace, passing neon for half an hour to eliminate the oxidizing atmosphere in the furnace chamber, and sintering the ingot in the sintering furnace at a temperature of 750° C. and a uniaxial pressure of 50 MPa at a heating rate of 15° C. / min for 1 hour to obtain a sintered aluminum alloy;
[0057] (5) Extruding, rolling and forging the sintered aluminum alloy of step (4) by equal-diameter angular extrusion to obtain a high-strength aluminum alloy;
[0058] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0059] The surface of the boron carbide is plated with an iron-nickel alloy layer;
[0060] The weight percentage of calcium in the calcium-aluminum alloy in step (2) is 10%.
[0061] Example 3
[0062] Preparation of high-strength aluminum alloy:
[0063] (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with the rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder;
[0064] (2) uniformly mixing 100 parts of the antioxidant aluminum powder described in step (1) with 3 parts of titanium nitride with an average particle size of 8 μm, 4 parts of boron carbide with an average particle size of 2 μm, 10 parts of nano zinc powder, 5 parts of vanadium powder, 2 parts of magnesium powder, 15 parts of calcium aluminum alloy powder, 1 part of zirconium dioxide powder, 1 part of borax powder, and 0.2 parts of gallium oxide powder according to weight parts to obtain a mixture;
[0065] (3) feeding the mixed material into a preset product mold of a press and compacting it at a pressing pressure of 1000 MPa to form a formed ingot, and demolding the ingot;
[0066] (4) placing the ingot of step (3) into a neon atmosphere sintering furnace, passing neon gas for half an hour to remove the oxidizing atmosphere in the furnace chamber, and sintering the ingot in the sintering furnace at a temperature of 850° C. and a uniaxial pressure of 20 MPa at a heating rate of 10° C. / min for 3 hours to obtain a sintered aluminum alloy;
[0067] (5) Extruding, rolling and forging the sintered aluminum alloy of step (4) by equal-diameter angular extrusion to obtain a high-strength aluminum alloy;
[0068] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0069] The surface of the boron carbide is plated with an iron-nickel alloy layer;
[0070] The weight percentage of calcium in the calcium-aluminum alloy in step (2) is 5%.
[0071] Example 4
[0072] Preparation of high-strength aluminum alloy:
[0073] (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with the rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder;
[0074] (2) uniformly mixing, by weight, 90 parts of the antioxidant aluminum powder described in step (1), 4 parts of titanium nitride with an average particle size of 6 μm, 3 parts of boron carbide with an average particle size of 4 μm, 11 parts of nano zinc powder, 4 parts of vanadium powder, 3 parts of magnesium powder, 14 parts of calcium aluminum alloy powder, 2 parts of zirconium dioxide powder, 0.6 parts of borax powder, and 0.4 parts of gallium oxide powder to obtain a mixture;
[0075] (3) feeding the mixed material into a product mold preset by a press and compacting it at a pressing pressure of 600 MPa to form a formed ingot, and demolding the ingot;
[0076] (4) placing the ingot of step (3) into a neon atmosphere sintering furnace, passing neon for half an hour to eliminate the oxidizing atmosphere in the furnace chamber, and sintering the ingot for 2 hours at a temperature of 820° C. and a uniaxial pressure of 40 MPa at a heating rate of 12° C. / min in the sintering furnace to obtain a sintered aluminum alloy;
[0077] (5) Extruding, rolling and forging the sintered aluminum alloy of step (4) by equal-diameter angular extrusion to obtain a high-strength aluminum alloy;
[0078] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0079] The surface of the boron carbide is plated with an iron-nickel alloy layer;
[0080] The weight percentage of calcium in the calcium-aluminum alloy in step (2) is 7%.
[0081] Comparative Example 1
[0082] Preparation of high-strength aluminum alloy:
[0083] (1) Put steel balls, aluminum blocks and lubricants into a ball mill, fill the ball mill and pipeline with nitrogen gas, and use the rolling steel balls to crush the aluminum blocks to obtain aluminum powder;
[0084] (2) uniformly mixing, by weight, 90 parts of the aluminum powder described in step (1), 4 parts of titanium nitride with an average particle size of 5 μm, 3 parts of boron carbide with an average particle size of 5 μm, 13 parts of nano zinc powder, 4 parts of vanadium powder, 2.5 parts of magnesium powder, 12 parts of calcium aluminum alloy powder, 2 parts of zirconium dioxide powder, 0.8 parts of borax powder, and 0.3 parts of gallium oxide powder to obtain a mixture;
[0085] (3) feeding the mixed material into a preset product mold of a press and compacting it at a pressing pressure of 800 MPa to form a formed ingot, and demolding the ingot;
[0086] (4) placing the ingot prepared in step (3) into a neon atmosphere sintering furnace, passing neon for half an hour to remove the oxidizing atmosphere in the furnace chamber, and sintering the ingot for 2 hours at a temperature of 800° C. and a uniaxial pressure of 30 MPa at a heating rate of 12° C. / min in the sintering furnace to obtain a sintered aluminum alloy;
[0087] (5) Extruding, rolling and forging the sintered aluminum alloy of step (4) by equal-diameter angular extrusion to obtain a high-strength aluminum alloy;
[0088] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0089] The surface of the boron carbide is plated with an iron-nickel alloy layer;
[0090] The weight percentage of calcium in the calcium-aluminum alloy in step (2) is 8%.
[0091] Comparative Example 2
[0092] Preparation of high-strength aluminum alloy:
[0093] (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with the rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder;
[0094] (2) uniformly mixing 90 parts of the antioxidant aluminum powder described in step (1) with 4 parts of titanium nitride with an average particle size of 5 μm, 13 parts of nano zinc powder, 4 parts of vanadium powder, 2.5 parts of magnesium powder, 12 parts of calcium aluminum alloy powder, 2 parts of zirconium dioxide powder, 0.8 parts of borax powder, and 0.3 parts of gallium oxide powder according to weight parts to obtain a mixture;
[0095] (3) feeding the mixed material into a preset product mold of a press and compacting it at a pressing pressure of 800 MPa to form a formed ingot, and demolding the ingot;
[0096] (4) placing the ingot prepared in step (3) into a neon atmosphere sintering furnace, passing neon for half an hour to remove the oxidizing atmosphere in the furnace chamber, and sintering the ingot for 2 hours at a temperature of 800° C. and a uniaxial pressure of 30 MPa at a heating rate of 12° C. / min in the sintering furnace to obtain a sintered aluminum alloy;
[0097] (5) Extruding, rolling and forging the sintered aluminum alloy of step (4) by equal-diameter angular extrusion to obtain a high-strength aluminum alloy;
[0098] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0099] The surface of the boron carbide is plated with an iron-nickel alloy layer;
[0100] The weight percentage of calcium in the calcium-aluminum alloy in step (2) is 8%.
[0101] Comparative Example 3
[0102] Preparation of high-strength aluminum alloy:
[0103] (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and the pipeline with nitrogen gas, crushing the aluminum blocks with the rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder;
[0104] (2) uniformly mixing, by weight, 90 parts of the antioxidant aluminum powder described in step (1), 4 parts of titanium nitride with an average particle size of 5 μm, 3 parts of boron carbide with an average particle size of 5 μm, 13 parts of nano zinc powder, 4 parts of vanadium powder, 2.5 parts of magnesium powder, 12 parts of calcium aluminum alloy powder, 2 parts of zirconium dioxide powder, 0.8 parts of borax powder, and 0.3 parts of gallium oxide powder to obtain a mixture;
[0105] (3) feeding the mixed material into a preset product mold of a press and compacting it at a pressing pressure of 800 MPa to form a formed ingot, and demolding the ingot;
[0106] (4) placing the ingot prepared in step (3) into a neon atmosphere sintering furnace, passing neon for half an hour to remove the oxidizing atmosphere in the furnace chamber, and sintering the ingot at 800° C. for 2 hours at a heating rate of 12° C. / min in the sintering furnace to obtain a sintered aluminum alloy;
[0107] (5) Extruding, rolling and forging the sintered aluminum alloy of step (4) by equal-diameter angular extrusion to obtain a high-strength aluminum alloy;
[0108] Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer;
[0109] The surface of the boron carbide is plated with an iron-nickel alloy layer;
[0110] The weight percentage of calcium in the calcium-aluminum alloy in step (2) is 8%.
[0111] Experimental example
[0112] The high-strength aluminum alloys prepared in Examples 1-3 and Comparative Examples 1-4 were tested for tensile strength, yield strength, friction resistance and density. The test methods are as follows:
[0113] The tensile strength is tested according to GB / T 16865-2023.
[0114] The yield strength is tested according to the standard of GB / T 3880.2-2006.
[0115] The abrasion resistance is tested according to GB / T 12967.1-2020.
[0116] The test data is shown in Table 1 below:
[0117] Table 1
[0118] Test items Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength(MPa) 656.3 655.6 655.9 656.2 520.3 453.4 513.8 Yield strength (MPa) 624.8 624.1 624.3 624.7 501.7 431.5 493.3 Friction resistance (mg) 12 13 13 12 26 35 27 Density(%) 99.8 99.4 99.3 99.6 85.2 96.3 76.5
[0119] It can be seen from Table 1 that the high-strength aluminum alloys prepared in Examples 1-4 of the present application have good strength, friction resistance and density.
[0120] The surface of the aluminum powder of the preparation raw material of Comparative Example 1 is not sprayed with epoxy zinc phosphate, and the rest is the same as Example 1. The tensile strength, yield strength, abrasion resistance and density of the high-strength aluminum alloy prepared in Comparative Example 1 are significantly inferior to those of Example 1 of the present application, indicating that the epoxy zinc phosphate of the present application not only has high strength, high toughness, and resistance to chemical corrosion, but also has excellent anti-rust and weather resistance. After being sprayed on the surface of aluminum powder, it can prevent the aluminum powder from contacting with the air and reduce the oxidation of the aluminum powder. The introduced phosphorus element forms a uniform alloying precipitate with aluminum, thereby improving the strength and toughness of the aluminum alloy.
[0121] The raw materials for the preparation of Comparative Example 2 do not contain boron carbide, and the rest are the same as Example 1. The strength and friction resistance of the high-strength aluminum alloy prepared in Comparative Example 2 are significantly inferior to those of Example 1 of the present application, indicating that the boron carbide particles of the present application can be used as a reinforcing phase to significantly improve the hardness and strength of the aluminum alloy.
[0122] In the preparation method of Comparative Example 3, no uniaxial pressure is applied during sintering, and the rest are the same as Example 1. The tensile strength, yield strength, wear resistance and density of the high-strength aluminum alloy prepared in Comparative Example 3 are significantly inferior to those of Example 1 of the present application, indicating that the ingot in the present application is subjected to sintering and hot pressing treatment, and metallurgical bonding is formed between the powder particles through the combined action of high temperature and pressure. The external pressure promotes slip and rearrangement between the powder particles, accelerates the material transfer process, thereby achieving rapid densification of the material and further improving the density and strength of the material.
[0123] Although the embodiments of the present application have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions or variations may be made to the embodiments without departing from the principles and purpose of the present application, and that the technical solutions after these changes, modifications, substitutions or variations will fall within the scope of protection of the present application.
Claims
1. A method for preparing a high-strength aluminum alloy, characterized in that: The following steps are involved: (1) placing steel balls, aluminum blocks and lubricants into a ball mill, filling the ball mill and a pipeline with inert gas, crushing the aluminum blocks with rolling steel balls to obtain aluminum powder, spraying epoxy zinc phosphate on the surface of the aluminum powder, and drying to obtain antioxidant aluminum powder; (2) uniformly mixing 80-100 parts of the antioxidant aluminum powder described in step (1) with 3-5 parts of titanium nitride, 2-4 parts of boron carbide, 10-15 parts of nano zinc powder, 3-5 parts of vanadium powder, 2-3 parts of magnesium powder, 10-15 parts of calcium aluminum alloy powder, 1-3 parts of zirconium dioxide powder, 0.5-1 parts of borax powder, and 0.2-0.5 parts of gallium oxide powder according to weight parts to obtain a mixture; (3) feeding the mixed material into a product mold preset in a press for compacting to form a formed ingot, and demolding the ingot; (4) placing the ingot described in step (3) into a protective atmosphere sintering furnace, passing the protective gas for half an hour to remove the oxidizing atmosphere in the furnace chamber, and sintering the ingot in the sintering furnace at a temperature of 750-850° C. and under a uniaxial pressure to obtain a sintered aluminum alloy; (5) Extruding, rolling and forging the sintered aluminum alloy in step (4) to obtain a high-strength aluminum alloy; Wherein, the surface of the titanium nitride is plated with a tin-lead alloy layer; The surface of the boron carbide is plated with an iron-nickel alloy layer.
2. The method for preparing a high-strength aluminum alloy according to claim 1, characterized in that: The weight percentage of calcium in the calcium aluminum alloy in step (2) is 5%-10%.
3. The method for preparing a high-strength aluminum alloy according to claim 1, characterized in that: The compaction pressure in step (3) is 100-1000 MPa.
4. The method for preparing a high-strength aluminum alloy according to claim 1, characterized in that: The heating rate of the sintering in step (4) is 10-15°C / min; the sintering time in step (4) is 1-3 hours.
5. The method for preparing a high-strength aluminum alloy according to claim 1, characterized in that: The uniaxial pressure during the sintering in step (4) is 20-50 MPa.
6. The method for preparing a high-strength aluminum alloy according to claim 1, characterized in that: The average particle size of the boron carbide is 2-8 μm, and / or the average particle size of the titanium nitride is 2-8 μm.
7. The method for preparing a high-strength aluminum alloy according to claim 1, characterized in that: The inert gas in step (1) is selected from one of nitrogen, helium, neon and argon, and / or the protective gas in step (4) is selected from one of nitrogen, helium, neon and argon.
8. The method for preparing a high-strength aluminum alloy according to claim 1, characterized in that: The extrusion in step (5) adopts equal-diameter angular extrusion.
9. A high-strength aluminum alloy made by the method for preparing a high-strength aluminum alloy as claimed in any one of claims 1 to 9.
10. Application of the high-strength aluminum alloy as claimed in claim 9 in automobile manufacturing and aerospace.